Peran Posyandu dalam Menigkatkan Kesehatan Masyarakat - Aldisa Raihan Fitrah; Binti Azizatun Nafi’ah (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Health has a very vital role for every human being, because without a healthy body condition, a person will experience difficulties in carrying out daily activities. Posyandu which is short for Integrated Service Post, is a Village/Sub-district Community Institution tasked with helping to improve basic social services in the health sector. This study looks at how the role of posyandu in improving public health in Tropodo Village, Waru District, Sidoarjo Regency, Indonesia. The method used is qualitative research with a descriptive approach through data collection through interviews and direct observation with related parties. This study uses the role theory according to Siagian 2018, namely Stabilizer, Innovator, Modernizer, Pioneer, and Implementer. In carrying out its role in improving public health, there are still obstacles such as the lack of implementation facilities and infrastructure and the persistence of individualistic communities. This study helps future authors regarding the role of posyandu in improving public health.